Entre imagens e imaginários urbanos: estudo iconográfico-iconológico acerca do patrimônio edificado na Belle Époque Amazônica em Manaus - Bruna Lopes de Andrade Martins (2023)
"Green Hell". “Paris of the tropics”. “Showcase city”. There are many images attributed to Manaus, capital of Amazonas in Brazil, over time. However, this universe of imaginaries is not restricted to intangible dimension, but is continuously manifested in production of space and is reflected in the field of cultural heritage. In the case of Historic City Centre, recently inscribed in the Books of Archaeological, Ethnographic and Landscape Tombo and Historic Tombo by National Historical and Artistic Heritage Institute (IPHAN), its formation process is directly associated with the so-called Amazonian Belle Époque, a moment of urban renewal that was developed by the rise of rubber export economy in the region, between the end of 19th century and the beginning of 20th century. The legacy of that period for the capital of Amazonas, in addition to the eclectic architecture, carries a considerable impact on the perception and relationship with the landscape. In that regard, this research discusses ways of looking at the built heritage of the Amazonian Belle Époque, in Manaus’s Center, through an iconographic and iconological study, as we understand the images as more than records of a certain space in time, but as a threshold of production and reproduction of imaginaries. Therefore, an interpretation of iconographic sources that represent Manaus of Belle Époque and its legacy was proposed, based on photographs and cards consulted in the collections of the Museum of Image and Sound of Amazonas (MISAM) and Public Archive of Manaus. Thus, it was possible to apprehend the fields of disputes and ideals of modernity present in the process of space’s consolidation as an asset of cultural value, starting from the idea that in case of images considered illusory or that do not correspond to the totality of what is understood by reality, the influence that manifests itself over time in the imaginary about the city center and in the values attributed to the protected site must be recognized.